"We have been forced to move away from home": print news coverage of Canadians studying abroad at Caribbean offshore medical schools. Issue 1 (December 2017) - Morgan, Jeffrey; Crooks, Valorie; Snyder, Jeremy
Abstract Background Canadian international medical graduates are Canadian-citizens who have graduated from a medical school outside of Canada or the United States. A growing number of Canadians enroll in medical school abroad, including at Caribbean offshore medical schools. Often, Canadians studying medicine abroad attempt to return to Canada for postgraduate residency training and ultimately to practice. Methods The authors conducted a qualitative media analysis to discern the dominant themes and ideologies that frame discussion of offshore medical schools, and the Canadian medical students they graduate, in the Canadian print news. We carried out structured searches on Canadian Newsstand Database for print media related to offshore medical schools. Results Canadian news articles used two frames to characterize offshore medical schools and the Canadian international medical graduates they train: (1) increased opportunity for medical education for Canadians; and (2) frustration returning to Canada to practice despite domestic physician shortages. Conclusion Frames deployed by the Canadian print media to discuss Caribbean offshore medical schools and Canadians studying abroad define two problems: (1) highly qualified Canadians are unable to access medical school in Canada; and (2) some Canadian international medical graduates are unable to return to Canada to practice medicine. Caribbean offshore medical schools are identified as a solution to the first problem while playing a central role in creating the second problem. These frames do not acknowledge that medical school admissions are a primary means to control the make-up of the Canadian physician workforce and they do not address the nature of Canadian physician shortages.